Breathe Safely with Low-Cost Portable Ventilator - Abhilash Krishnan A,; Analram V S,; Abhinav P,; Archana S,; S. Swapna Kumar, (International Journal of Engineering and Technology, 2024)
The global healthcare landscape has been profoundly impacted by the COVID-19 pandemic, highlighting the urgent need for a robust and adaptable healthcare infrastructure to navigate public health crises effectively. In response to this imperative, a project was initiated to develop a low-cost portable ventilator system that embodies key attributes of affordability, rapid deployability, and scalability. This paper provides a comprehensive exploration of the design principles, challenges, and ethical considerations associated with the development of low-cost ventilators, emphasizing the critical importance of clear documentation, rigorous testing, and regulatory compliance in the realm of open-source ventilator design. Through a meticulous process of research and testing, the ventilator system has been meticulously evaluated and validated for clinical applications across diverse healthcare settings. The findings of this project not only validate the feasibility and efficacy of the ventilator system but also underscore its potential to address critical gaps in emergency respiratory support. This innovative solution represents a significant technological milestone in reshaping the landscape of emergency respiratory care, offering a scalable and affordable alternative to traditional ventilator systems. The development of this low-cost portable ventilator system stands as a testament to the power of innovation and collaboration in addressing pressing healthcare challenges. By enhancing global health preparedness and resilience through the creation of accessible and efficient medical technologies, this project paves the way for a more secure and adaptable healthcare infrastructure capable of meeting the demands of future public health crises.